Review of Privacy vs Security - Nieuwenhuis, Aernout (Utrecht Journal of International and European Law, 2015)
Privacy vs Security, Sophie Stalla-Bourdillon, Joshua Philips and Mark D. Ryan, Springer, Springer Briefs in Cybersecurity, pp. 1–115, Softcover: €52.99, 2014, ISBN: 9781447165293